2006
DOI: 10.1152/ajplung.00031.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma fermentansand TNF-β interact to amplify immune-modulating cytokines in human lung fibroblasts

Abstract: Mycoplasma can establish latent infections and are associated with arthritis, leukemia, and chronic lung disease. We developed an experimental model in which lung cells are deliberately infected with Mycoplasma fermentans. Human lung fibroblasts (HLF) were exposed to live M. fermentans and immune-modulating cytokine release was assessed with and without known inducers of cytokine production. M. fermentans increased IL-6, IL-8/CXCL8, MCP-1/CCL2, and Gro-α/CXCL1 production. M. fermentans interacted with TNF-β to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…We cannot, however, fully exclude the possibility that trace amounts of Ni remain within the cell even after vigorous washing and contribute to the response. We have previously observed a similar effect of facilitation of MALP-2-dependent IL-6 release following pre-exposure of HLF to TNF-β, an extracellular protein ligand that is likely more confidently removed with washing (Fabisiak et al , 2006). The addition of Ni (or TNF) along with the MALP-2 challenge, however, does further enhance the response indicating that maximal effects can be better realized with concurrent exposure to both agonists.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We cannot, however, fully exclude the possibility that trace amounts of Ni remain within the cell even after vigorous washing and contribute to the response. We have previously observed a similar effect of facilitation of MALP-2-dependent IL-6 release following pre-exposure of HLF to TNF-β, an extracellular protein ligand that is likely more confidently removed with washing (Fabisiak et al , 2006). The addition of Ni (or TNF) along with the MALP-2 challenge, however, does further enhance the response indicating that maximal effects can be better realized with concurrent exposure to both agonists.…”
Section: Discussionmentioning
confidence: 68%
“…Individual cell lines prepared from previously frozen stocks were propagated in Minimal Essential Medium (MEM) supplemented with fetal bovine serum (10%, final concentration), glutamine (2 mM), penicillin (100 U/ml), streptomycin (100 μg/ml) in a humidified incubator with 5% CO 2 /95% air as previously described (Fabisiak et al , 2006). All cultures were negative for mycoplasma as determined by fluorescent microscopy using Hoechst 33258 (Chen, 1977) or MycoAlert ™ mycoplasma detection kit (Cambrex BioScience, Rockland, ME).…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that colonization with species originally considered commensal and not causing overt disease (e.g., Mycoplasma fermentans) also has the potential to interact with other stimuli and/or alter biological responses in infected host cells (5,6). For example, we have previously shown that exposure of human lung fibroblast cells (HLF) to M. fermentans synergistically enhances the release of IL-6 by PM in the form of residual oil fly ash (ROFA) compared to either stimulus alone (7).…”
mentioning
confidence: 99%
“…This study showed the ability of Mycoplasma fermentans to persist in different organs for at least 50 days after inoculation, probably because they can evade the immune system and enter the cells where the antibodies and antibiotics cannot act and induce a chronic inflammation [18]. Intensive studies have been done in order to understand the strategy used by Mycoplasma fermentans to interact with host cells and evade the host protection system.…”
Section: Resultsmentioning
confidence: 99%
“…Mycoplasma fermentans serves as a stimulus for the production of several immune modulating cytokines and components of an inflammatory response. Mycoplasma may modulate inflammatory and immune processes within the lung as well as potentiate T cell dependent immunopathologies [18]. …”
Section: Resultsmentioning
confidence: 99%